Pleasure: An under-utilised ‘P’ in social marketing for healthy eating - Pettigrew, Simone (Elsevier BV, 2015)
The escalating obesity crisis has resulted in a wide range of efforts to develop more effective prevention approaches. This review article explores the potential for the concept of food pleasure to take centre stage in social marketing programs that aim to encourage healthy eating. Literature relating to food motivations is reviewed and the various strategic phases involved in developing social marketing programs are outlined in the context of incorporating a food pleasure focus.